Cities and regions in the new learning economy - Miszczak, Katarzyna (Miasta i regiony w nowej gospodarce uczącej się, 2016)
The features of the learning economy and the modern challenges for regional and urban policy were briefly characterized in the paper. Special attention was paid to the specificity of functioning of the learning cities-regions under new economic conditions. Based on the chosen definitions of a knowledge, information and ICT sector, the rules of learning process applicable in the territorial units were generally described
Biblioteka Regionalisty, 2016, Nr 16, s. 63-74
Keywords: learning economy; knowledge; city; region; gospodarka ucząca się; wiedza; miasto